2019
DOI: 10.1007/s12630-019-01492-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for reintubation after anterior cervical discectomy and fusion surgery: evaluation of three observational data sets

Abstract: Purpose Postoperative loss of airway requiring reintubation is a rare but potentially catastrophic complication following anterior cervical discectomy and fusion (ACDF). We sought to identify risk factors asscociated with reintubation within one day following ACDF. Attention was focused on patient demographics, comorbidities, and factors potentially linked to soft tissue swelling and hematoma formation that could compromise the upper airway. Methods We performed a retrospective cohort study of patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
3
17
1
Order By: Relevance
“…were associated with a higher risk of unplanned re-intubation. 28 There are several potential limitations inherent to this study. First, the sample of patients undergoing ACDF may not have been accurately representative of all the patients who undergo ACDF.…”
Section: Discussionmentioning
confidence: 96%
“…were associated with a higher risk of unplanned re-intubation. 28 There are several potential limitations inherent to this study. First, the sample of patients undergoing ACDF may not have been accurately representative of all the patients who undergo ACDF.…”
Section: Discussionmentioning
confidence: 96%
“…While previous studies have identified the incidence and risk factors for RC, 24 , 28 , 33 none have fully defined the short-term clinical course of patients who develop RC. This study demonstrates that patients who develop RC have high rates of both morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated increased pre-vertebral soft tissue swelling as a function of number of levels fused, corpectomies, and upper cervical spine surgery. 31,32 While previous studies have identified the incidence and risk factors for RC, 24,28,33 none have fully defined the shortterm clinical course of patients who develop RC. This study demonstrates that patients who develop RC have high rates of both morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a total of 10 studies and 5,15,940 patients were included in this metaanalysis. (1,3,(13)(14)(15)(16)(17)(18)(19) The selection process and results are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%